2014
DOI: 10.4172/2161-0940.1000162
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Duplication of the Foramen Spinosum: A Case Report with Clinical and Developmental Implications

Abstract: In humans, the foramen spinosum (FS) is located within the sphenoid bone and transmits the middle meningeal artery (MMA). In species that evolutionarily predate humans, the FS exists within the temporal bone, the sphenosquamosal suture, or is absent altogether. It is therefore thought that, during the course of human evolution, the ossification of the posterior aspect of the greater wing of the sphenoid progressively developed around the MMA. The report documents the occurrence of a bilateral duplication of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
(19 reference statements)
0
1
0
1
Order By: Relevance
“…5 In the literature, variations such as absence, small size, or duplication of the foramen spinosum have been reported to be rare. [7][8][9] Khan et al 7 reported that the foramen spinosum was absent in 0.4% of cases and stated that the middle meningeal artery may arise from the ophthalmic artery in these cases. In rare cases, the foramen spinosum may be small.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 In the literature, variations such as absence, small size, or duplication of the foramen spinosum have been reported to be rare. [7][8][9] Khan et al 7 reported that the foramen spinosum was absent in 0.4% of cases and stated that the middle meningeal artery may arise from the ophthalmic artery in these cases. In rare cases, the foramen spinosum may be small.…”
Section: Discussionmentioning
confidence: 99%
“…6 Previous studies have reported absence, small size and/or duplication of the foramen spinosum is rarely seen. [7][8][9] This study aims to report a case with duplicated foramen spinosum on one side and absent foramen spinosum on the other side and discuss the possible clinical implications of this variation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…FS sphenoid kemiğin ala major bölgesinde yer alan, fossa crani media ile fossa infratemporalis arasındaki bağlantıyı sağlayan yapılardan bir tanesidir 3 . Duplike olması, unilateral veya bilateral eksikliği, gibi varyasyonlarının yanı sıra bilateral simetri durumu, uzunluğu, genişliği, alanı ve çevresi gibi parametreler de oldukça önemlidir 7 . Çünkü FS'nin morfolojisi ve morfometrik yapısı ile içinden geçen MMA arasında bir ilişki vardır 3 .…”
Section: Discussionunclassified
“…40,41 A line was drawn through the basilar process of the occiput to identify the midsagittal plane in order to orient the digital image appropriately for measurement with ImageJ software. 42,43 …”
Section: Methodsmentioning
confidence: 99%